The Image of Future Human Represented in Chappie (2015) - Muchammad Sofyan Firmansyah (Humanitatis : Journal of Language and Literature, 2022)
This research discussed the image of the future human which is represented in Chappie (2015) movie by using representation theory. The researcher focused on the way the movie director created the figure of the future humans in his movie. The implementation of representation theory is used to analyze the image of the future humans created by the movie maker in Chappie (2015) movie. Chappie is a robot that has artificial intelligence to support itself in making decisions toward its acts. Furthermore, Chappie which is an Artificial Intelligence human-robot occurs as the most suitable figure to represent the human in the future era.